Primary health insurance and cardiovascular outcomes in the systolic blood pressure intervention trial. (14th October 2021) - Byrne, C; Pareek, M; Vaduganathan, M; Mikkelsen, A D; Kristensen, A M D; Biering-Sorensen, T; Kragholm, K H; Mortensen, M B; Singh, A; Olsen, M H; Bhatt, D L
Abstract: Background: The Systolic Blood Pressure Intervention Trial (SPRINT) found that intensive versus standard blood pressure (BP) control reduced cardiovascular (CV) morbidity and mortality in high-risk patients. Although antihypertensive therapies were provided at no cost to trial participants, patients were covered by various entities. Insurance coverage provides a unique dimension of risk assessment and may provide additional prognostic information in this setting. Purpose: To assess the risks of incident CV events and safety events in a high CV risk population according to type of health insurance, and to assess if insurance type interacted with the effect of intensive versus standard BP control. Methods: SPRINT was a randomized, controlled trial conducted across 102 US sites of 9, 361 high-risk adults ≥50 years, without diabetes, and with a systolic BP 130–180 mmHg at screening. Study participants were randomized to intensive (target systolic BP <120mmHg) or standard BP control (target systolic BP <140mmHg) and followed for median 3.2 years (range 0–4.8 years). The primary efficacy endpoint was the composite of acute coronary syndromes, stroke, heart failure, or CV death. The primary safety endpoint was the composite of serious adverse events. The risk of efficacy and safety events according to type of health insurance, including the effect of intensive BP control in each subgroup, was evaluated using multivariable Cox proportional-hazards regression with interaction analyses. Private/other insurance type served as the reference group. Results: Of 9361 participants, 3980 (42.5%) were covered by private/other insurance, 1483 (15.8%) by a Veterans Affairs (VA) health plan, 2691 (28.8%) by Medicare, 207 (2.2%) by Medicaid, and 1000 (10.7%) were uninsured. Insurance coverage distribution was well-balanced between the two study arms (P>0.05). Compared with patients who had private/other insurance, the risk of the primary endpoint was significantly higher among Medicaid beneficiaries (adj. hazard ratio [HR], 1.81, 95% confidence interval [CI], 1.09–3.00; P=0.02). The risk of death was similarly highest among Medicaid patients (adj. HR, 2.08, 95% CI, 1.08–4.02; P=0.03) and was also significantly higher among VA patients (adj. HR, 1.49, 95% CI, 1.11–2.99; P=0.008) (Figure). Serious adverse events were more common in the VA population (HR, 1.12, 95% CI, 1.01–1.23; P=0.03). Insurance type did not modify the efficacy and safety of intensive BP control (P>0.05 for all interactions). Conclusions: In SPRINT, Medicaid beneficiaries were at significantly greater risk for experiencing a primary CV event. Medicaid patients and VA patients both had higher mortality than those covered by private/other insurance. The risks and benefits of intensive BP control were not affected by insurance type. FUNDunding Acknowledgement: Type of funding sources: None.